Numerical Simulation of Fluid Flow in the Narrow Strait with Density Differences - Usman, Tarmizi; Ikhwan, Muhammad; Zulfataya, Muhammad; Adami, Farhan (JTAM (Jurnal Teori dan Aplikasi Matematika), 2025)
This study investigates the dynamics of fluid flow through a narrow strait connecting two large water bodies with different densities using numerical simulations. The research focuses on understanding how density-driven currents develop and interact in a confined channel, particularly the role of lateral density contrasts and the influence of gravitational and geostrophic forces. A semi-implicit numerical method is employed to efficiently model the complex flow dynamics while ensuring stability. The simulation results are analyzed using visualizations of the flow fields, which highlight the evolution of density-driven currents, vortex formation, and geostrophic adjustments over time. The findings reveal that denser water from the western basin flows toward the eastern basin, lowering the sea surface in the west and raising it in the east. Over time, the Coriolis force causes the bottom flow to deflect southward and the returning surface flow to shift northward, leading to geostrophic equilibrium. Transient vortices emerge within the strait, while stationary vortices form in the outflow regions, underscoring the interplay between gravitational forces, density contrasts, and rotational effects. These findings offer important insights into the hydrodynamic behavior of narrow straits, which are common in nature. The results can help improve the understanding of flow patterns in similar environments, such as fjords, estuaries, and channels, and may contribute to studies on sediment transport, nutrient mixing, and renewable energy potential in density-driven systems.